Elm Slough, Pottawatomie County - Strathe, Erin (Kansas State University, The Chapman Center for Rural Studies, 2012)
The author uses oral interview and historic documents to reconstruct the details of the little community of Elm Slough in Pottawatomie County, Kansas.
Erin Strathe, “Elm Slough, Pottawatomie County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/91.
Keywords: Delores Lambrecht; Elm Slough; Flush Road; One-room School; Pottawatomie County; Westmoreland Recorder